Continuing education credit workshops - Buffington, E. J., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet describes how to request approval for continuing education credit workships and defines each subject area.
CEPEP 10/01, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticide applicators (Persons) -- Education (Continuing education); Pesticides -- Application -- Colorado